Association study of toll-like receptors 4 polymorphisms and the risk of age-related macular degeneration: a meta-analysis. (1st November 2020) - Zhou, Jian-Ying; Huang, Yi-Qian; Zhang, Xiao-Yan; Zheng, Pei-Fen; Li, Peng; Chen, Yan; Shu, Long
ABSTRACT: Background: Toll-like receptor 4 (rs4986790, rs4986791) single nucleotide polymorphisms (SNPs) have been shown to be associated with age-related macular degeneration (AMD), but the results are still inconclusive. The present meta-analysis was conducted to evaluate the association between SNPs of TLR4 gene and AMD susceptibility. Methods: Relevant articles were obtained through computer retrieval of Pubmed, Embase, Chinese National Knowledge Infrastructure and China wanfang database. Eligible articles were selected according to the inclusion and exclusion criteria, and quality scores were made for them by NOS-scale. Relevant data were extracted for meta-analysis. The combined OR value and 95% confidence interval were used to evaluate the strength of the correlation. Funnel plot and Egger's regression were used to evaluate publication bias. All analyses were performed using STATA 11.0 software. Results: A total of nine case-control studies were included in this meta-analysis. After combination, an significant association was found between rs4986790 polymorphism and AMD susceptibility in heterozygote model (AG vs. AA, OR = 1.400, 95%CI = 1.049–1.867, P = .022) and dominant model (GG+AG vs. AA, OR = 1.365, 95%CI = 1.028–1.813, P = .032). There was no association found between rs4986791 polymorphism and AMD susceptibility in all genetic models (all P > .05). Funnel plot and Egger's regression analysis showed no publication bias existed in this study. Conclusions: Meta-analysis suggested that there is an association between TLR4 gene rs4986790 polymorphism and AMD susceptibility, while no association between rs4986791 polymorphism and AMD susceptibility.